The Talangsari Incident in Lampung in 1989: A Review of Social History - Bobi Hidayat; Johan Setiawan (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The purpose of this paper is to describe the Talangsari incident from the point of view of the social history of a historical event. The social life before the incident, when warsidi in the village of Talang Sari, and after the Talang Sari incident became the object of study and discussion in this paper. The research method used is the historical method with steps including heuristics, source criticism (internal and external), interpretation, and historiography. Based on the results of the study, it was shown that the social conditions of the people of Talang Sari III Hamlet before the arrival of Warsidi and his group were running peacefully because there were no different views. Social relations are going well without any significant conflict. After the arrival of warsidi and his group then settled, many problems occurred including many community plantation products that were taken without the permission of the owner. This triggered social interaction that was not good between Warsidi's group and the surrounding community. In addition, the closure of the warsidi group further adds to the social interaction between the warsidi and his group and the surrounding community. After the Talangsari incident, the social conditions of the people tended to improve, but some problems arose afterward. In addition to the surviving warsidi followers experiencing social difficulties, they also find it difficult to blend in with the surrounding community.